Optimization of Higher Alkanes Dehydrogenation Process under Conditions of Decreased Hydrogen Containing Gas Flow with Using Mathematical Modeling - Ivanchina E. D. Emilia Dmitrievna; Ivashkina E. N. Elena Nikolaevna; Glik P. A.; Platonov V. V.; Dolganov I. M. Igor Mikhailovich (2015, 2015)
Title screen